2007
DOI: 10.1002/rmv.554
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral treatment of chronic hepatitis B virus infections: the past, the present and the future

Abstract: A decade ago, standard therapy against chronic hepatitis B virus infections only consisted of lamivudine or IFN-alpha. Treatment with lamivudine and IFN has been compounded by, respectively, the emergence of drug-resistant virus strains and the appearance of serious side effects. In the last 10 years, hepatitis B treatment has made much progress. Several treatments are now licensed for the treatment of patients with chronic hepatitis B and others are under development. Here, we provide an overview of the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
44
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 128 publications
0
44
0
1
Order By: Relevance
“…Nucleoside analogs have long been the backbone therapy for the treatment of viral diseases such as HIV, HBV, and HSV infections (1)(2)(3)(4)(5). Recent studies have suggested that nucleoside analogs may be useful for treating hepatitis C virus (HCV) 3 infection (4, 6 -8).…”
mentioning
confidence: 99%
“…Nucleoside analogs have long been the backbone therapy for the treatment of viral diseases such as HIV, HBV, and HSV infections (1)(2)(3)(4)(5). Recent studies have suggested that nucleoside analogs may be useful for treating hepatitis C virus (HCV) 3 infection (4, 6 -8).…”
mentioning
confidence: 99%
“…21 The anticancer drug oxaliplatin, 22,23 the histamine H 2 receptor antagonist cimetidine, 24,25 and the antiviral drug lamivudine 19,20 are substrates for both OCT1 and OCT3. Notably, hepatocytes are the pharmacological target cells of lamivudine, when it is used to treat chronic hepatitis B, 26 and of metformin. 27 The impact of an altered OCT1-mediated drug transport on pharmacokinetics can be exemplified by metformin.…”
mentioning
confidence: 99%
“…Current treatments are unable to clear viral infection and are prone to the appearance of drug-resistant mutants (4)(5)(6)(7)(8). Efforts to produce better treatments remain an active goal of HBV research.…”
mentioning
confidence: 99%